2014
DOI: 10.1093/neuonc/nou059
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of sorafenib in children with recurrent or progressive low-grade astrocytomas

Abstract: Sorafenib produced unexpected and unprecedented acceleration of tumor growth in children with PLGA, irrespective of NF1 or tumor BRAF status. In vitro studies with sorafenib indicate that this effect is likely related to paradoxical ERK activation. Close monitoring for early tumor progression should be included in trials of novel agents that modulate signal transduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 32 publications
6
151
3
3
Order By: Relevance
“…The experience of use of SHH pathway inhibitors in pancreatic cancer, or BRAF inhibitors in BRAF-fusion gene-positive low-grade gliomas highlights this best, as treatment was found to promote rather than inhibit tumor growth. 27,32,43 …”
Section: Molecular Biology Of Tumor Recurrencementioning
confidence: 99%
“…The experience of use of SHH pathway inhibitors in pancreatic cancer, or BRAF inhibitors in BRAF-fusion gene-positive low-grade gliomas highlights this best, as treatment was found to promote rather than inhibit tumor growth. 27,32,43 …”
Section: Molecular Biology Of Tumor Recurrencementioning
confidence: 99%
“…Initial experiences with certain chemotherapy regimens [i.e., cisplatin/carboplatin and etoposid; (Tsugu et al, 2009)] applied to PMAs provided promising results and underline the importance of further research of aggressive therapy strategies often required by PMA. In addition, there are ongoing discussions regarding the question if PMA and PA patients may qualify for a novel therapeutic approach with inhibitors targeting the RAF/MAPK/ERK pathway that was found to be activated in almost all tumors (Aktas et al, 2014;Karajannis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to inhibit tumor growth in a mouse plexiform model [112]. Unfortunately, it was not tolerated by pediatric patients in a Phase I study [113] and either no tumor response or acceleration of tumor progression was observed in studies on OPG (NCT01338857) [114], PNF (NCT00727233) [113] and MPNST (NCT00245102).…”
Section: • Sunitinibmentioning
confidence: 99%